N-rGO@NiCo catalyst loaded LiAlH4 composite material, preparation method and application
By introducing N-rGO@NiCo catalyst into LiAlH4 material, the problems of poor reversibility, high hydrogen release temperature and slow rate of the material are solved, and more efficient hydrogen release and reversible hydrogen storage performance are achieved.
Patent Information
- Application Number
- CN202410447125.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-04-15
AI Technical Summary
The existing LiAlH4 materials have problems such as poor reversibility, high hydrogen release temperature in the second step, and slow hydrogen release rate, which limits their application in the field of solid hydrogen storage.
Nitrogen-doped graphene was prepared by hydrothermal synthesis and lyophilization using N-rGO@NiCo catalyst-supported LiAlH4 composite material, and nitrogen-doped graphene was then anchored on its surface, and a high specific surface area material was obtained by impregnation of aluminum lithium hydride.
The hydrogen release temperature of the material is significantly reduced, the hydrogen release amount and reversibility are improved, which is specifically manifested as the hydrogen release temperature drops to 103°C, which can release 3.8% of hydrogen in 300°C, and improves the reversible hydrogen storage performance.
Smart Images

Figure HDA0004791388830000011 
Figure HDA0004791388830000012 
Figure HDA0004791388830000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid-state hydrogen storage, and in particular relates to a N-rGO@NiCo catalyst-loaded LiAlH4 composite material, a preparation method and an application thereof. Background Art
[0002] Energy depletion has become a common problem faced by mankind. Finding green, efficient and renewable new energy to replace fossil energy has become the development goal of countries around the world and has been widely studied by the academic community. Hydrogen energy has become one of the most promising alternative energy sources due to its high calorific value, environmental protection, pollution-free and renewable advantages. At present, the development and utilization of hydrogen energy mainly faces three key issues: production, storage and transportation. Among them, how to store hydrogen energy safely and efficiently as on-board is currently the most challenging and commercially valuable research topic. The low efficiency and low safety of traditional high-pressure liquid and gaseous hydrogen storage have become important factors restricting the large-scale commercialization of on-board hydrogen storage. Solid-state hydrogen storage, as a hydrogen storage method with large hydrogen storage capacity, has the advantages of low energy consumption, high hydrogen storage capacity and low cost. It has great research potential and is currently the most popular hydrogen storage direction being studied.
[0003] In the research of solid-state hydrogen storage, LiAlH4 coordination hydride has a high hydrogen storage capacity of up to 10.9wt% and the lowest initial dehydrogenation temperature among coordination hydrides, which has attracted extensive attention. However, LiAlH4 has a high actual dehydrogenation temperature and a slow dehydrogenation rate, which makes it unable to match the dehydrogenation temperature of fuel cells, greatly limiting the application of this material. At present, catalytic doping combined with nano-sizing is an effective method to improve the dehydrogenation temperature and reversibility of the material.
[0004] Lei (Zang L, Liu S, Guo H, et al. In Situ Synthesis of 3D Flower-LikeNanocrystalline Ni / C and its Effect on Hydrogen Storage Properties of LiAlH4[J]. Chemistry–An Asian Journal, 2018, 13(3): 350-357.) et al. used in situ formed Ni / C nanoflowers to introduce LiAlH4 by ball milling. The initial dehydrogenation temperature of the material dropped to about 48°C. Under isothermal conditions of 140 degrees, the material was able to release about 4.3wt% of hydrogen and obtained limited reversibility under a hydrogen pressure of 5.5MPa. The rehydrogenation product could only be detected under FT-IR. Bu (Bu Y, Sun L, Xu F, et al. Highly active bimetallic MOF derivatives for improving the dehydrogenation performance of LiAlH4[J]. Journal of Alloys and Materials Compounds, 2023, 961: 170897.) and others introduced highly active MOF into the material by ball milling. The dehydrogenation temperature of LiAlH4 was reduced to about 84.1°C, and a rehydrogenation capacity of about 0.6 wt% was obtained. Therefore, the catalytically modified supported material will have a very important improvement effect on the material performance, especially the improvement of the reversibility of LiAlH4.
[0005] However, the above materials still have problems such as poor reversibility, high hydrogen desorption temperature in the second step, and slow hydrogen desorption rate. Summary of the invention
[0006] The present invention provides a N-rGO@NiCo catalyst-loaded LiAlH4 composite material, a preparation method and an application thereof, which solve the problems of poor material reversibility, high second-step hydrogen desorption temperature and slow hydrogen desorption rate in the prior art.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] In the first aspect, the present invention provides a N-rGO@NiCo catalyst loaded LiAlH4 composite material, the composite material is named N-rGO@NiCo / LiAlH4, the mass ratio range of each component is N-rGo:NiCo:LiAlH4=15-49.9:0.1-5:50-80, and the macroscopic morphology of the composite material is solid nanoparticles.
[0009] Furthermore, the mass ratio of each component is: N-rGo:NiCo:LiAlH4=49.5:0.5:50.
[0010] Furthermore, the NiCo is in the form of bimetallic single atoms.
[0011] In a second aspect, the present invention provides a method for preparing a N-rGO@NiCo catalyst-loaded LiAlH4 composite material, comprising:
[0012] S1. Preparation of nitrogen-doped graphene aerogel;
[0013] S2. Preparing NiCo modified nitrogen-doped graphene aerogel, comprising:
[0014] S201. Weigh the nitrogen-doped graphene aerogel and place it in a container;
[0015] S202. Weigh the nickel source and cobalt source precursors of the catalyst, dissolve them in anhydrous ethanol to form solution A, pour solution A into a container containing the nitrogen-doped graphene aerogel, and solution A needs to immerse the nitrogen-doped graphene aerogel; the mass ratio of the catalyst precursor to the mass of N-rGo is in the range of 1-15:100.
[0016] S203. The container containing solution A is placed on a magnetic stirrer and stirred thoroughly. After ultrasonic treatment for 30 minutes, the anhydrous ethanol in solution A is evaporated and then dried at 45-150° C. to obtain material B;
[0017] S204. The material B is placed in a porcelain boat and transferred to a tube furnace. Under an inert gas, the temperature is increased from room temperature to 150-500°C at a rate of 2-10°C per minute and maintained for 3-10 hours; then washed with a water-ethanol mixture and filtered three times, and transferred to an 80°C oven for drying to obtain material C;
[0018] S205. The material C is transferred to a tube furnace again, and under an inert gas flow, the temperature is increased from room temperature to 400-750° C. at a rate of 2-10° C. per minute and maintained for 3-10 h to obtain a material D;
[0019] S206. Transfer material D to an argon glove box, remove the adsorbed moisture in a tube furnace at 60-200° C. in vacuum to obtain NiCo-modified nitrogen-doped graphene aerogel.
[0020] S3. The NiCo-modified nitrogen-doped graphene aerogel is impregnated with lithium aluminum hydride, comprising:
[0021] S301. Weigh lithium aluminum hydride and transfer it to a reagent bottle;
[0022] S302. The calcium hydride is dried and filtered and ether is added to the reagent bottle and stirred to obtain a solution B;
[0023] S303. The solution B is drawn into the syringe and impregnated dropwise onto the NiCo-modified nitrogen-doped graphene aerogel to ensure that the NiCo-modified nitrogen-doped graphene aerogel is fully infiltrated;
[0024] S304. The infiltrated NiCo-modified nitrogen-doped graphene aerogel was transferred to a tubular furnace and vacuum dried at room temperature for 12 h to obtain the final product.
[0025] Further, S1. preparing nitrogen-doped graphene aerogel, comprising:
[0026] S101. Configuring a graphene oxide aqueous solution, wherein the concentration of the graphene oxide aqueous solution is 1-10 mg / ml;
[0027] S102. Weigh urea and dissolve it in the graphene oxide aqueous solution, wherein the mass ratio of urea to graphene oxide is 10-0.1:1, and then place it in an ultrasonic machine for 0.5-5h to obtain a solution C;
[0028] S103. Solution C is placed in a hydrothermal reactor and subjected to hydrothermal treatment at 120-200° C. for 12-48 h to obtain a hydrogel;
[0029] S104. Soaking the hydrogel in deionized water for 6-72 hours, changing the water every 0.5-5 hours;
[0030] S105. Obtain the nitrogen-doped graphene aerogel after freeze-drying.
[0031] Furthermore, the nickel source and cobalt source precursors include NiCl2H2O, CoCl26H2O or Ni(NO3)2, Co(NO3)2 or Co(CH3COO)2, Ni(CH3COO)2.
[0032] Furthermore, in S203 and S204, the inert gas is selected from nitrogen or argon.
[0033] Furthermore, before taking out the final product, the attached ether was removed by heating the tube furnace at 40-90°C.
[0034] In a second aspect, the present invention provides an application of a N-rGO@NiCo catalyst-loaded LiAlH4 composite material in a solid hydrogen storage material.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The method of the present invention prepares nitrogen-doped graphene through hydrothermal synthesis and freeze-drying, then anchors a small-sized catalyst on the surface of the nitrogen-doped graphene through a two-step calcination method, and finally obtains a high specific surface area material by impregnating the catalyst. The method is simple, low-cost, and the synthetic product is stable, which is suitable for promotion.
[0037] 2. The dehydrogenation temperature of the N-rGo@NiCo / LiAlH4 composite material prepared by the present invention is reduced to 103°C, and 3.8wt% of hydrogen can be released within 300°C; the dehydrogenation activation energy is reduced to 60.717 kJ·mol -1 and 103.855 kJ·mol -1 , compared with the original LiAlH4 material performance has been greatly improved.
[0038] 3. The N-rGo@NiCo / LiAlH4 composite material prepared by the present invention is at 150°C, wherein the loading amount of LiAlH4 is 50wt.%, so the reversibility of the original LiAlH4 material after isothermal hydrogen absorption at 10Mpa will reach 1.2wt.%, which greatly improves the reversible hydrogen storage performance of the material.
[0039] 4. The N-rGo@NiCo / LiAlH4 composite material prepared by the present invention can form nanoparticles with smaller particle size on the surface through the restriction effect of the interface due to the large specific surface area of graphene, and the single atom / small-size catalyst modified on the surface of graphene restricts the diffusion of the material and has a strong catalytic effect. The above two points jointly promote the improvement of the reversibility of the composite material.
[0040] Of course, the implementation of the various technical solutions of the present invention does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, drawings of other embodiments can be obtained based on these drawings without paying creative work.
[0042] Figure 1 SEM images of the N-rGo@NiCo / LiAlH4 composite material prepared in Example 1 at different magnifications;
[0043] Figure 2 X-ray diffraction patterns of the N-rGo@NiCo / LiAlH4 composite material prepared in Example 1 and N-rGo@NiCo before loading LiAlH4;
[0044] Figure 3 TEM images and element distribution analysis diagram of N-rGo@NiCo before and after loading LiAlH4 prepared in Example 1;
[0045] Figure 4 This is a non-isothermal hydrogen desorption performance diagram of the N-rGo@NiCo / LiAlH4 composite material obtained in Example 1;
[0046] Figure 5 It is the non-isothermal hydrogen desorption performance diagram of the LiAlH4 composite material with Ni and Co elements loaded separately in the comparative example;
[0047] Figure 6 This is the rehydrogenation capacity diagram of the N-rGo@NiCo / LiAlH4 composite material obtained in Example 1;
[0048] Figure 7 FT-IR infrared absorption spectrum of N-rGo@NiCo / LiAlH4 composite material obtained in Example 1;
[0049] Figure 8 The isothermal dehydrogenation curves of the N-rGo@NiCo / LiAlH4 composite material prepared in Example 1 at different temperatures;
[0050] Fig. 9 Temperature change and hydrogen mass spectrometry of the N-rGo@NiCo / LiAlH4 composite material obtained in Example 1 at heating rates of 3K / min, 5K / min, and 10K / min;
[0051] Fig.10 This is the double spherical aberration corrected TEM image of the N-rGo@NiCo / LiAlH4 composite material prepared in Example 1 at high magnification. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are for making the present application better understood. However, those skilled in the art can easily recognize that some features can be omitted in different situations, or can be replaced by other elements, materials, methods. In some cases, some operations related to the present application are not shown or described in the specification, this is to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.
[0053] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.
[0054] Some of the terms involved in the present invention are explained as follows:
[0055] LiAlH4: lithium aluminum hydride;
[0056] NiCo: Cobalt-nickel bimetallic;
[0057] N-rGo: nitrogen-doped graphene;
[0058] N-rGo@NiCo: NiCo modified nitrogen-doped graphene;
[0059] The present invention provides a N-rGO@NiCo catalyst-loaded LiAlH4 composite material, a preparation method and an application thereof. The preparation method of the composite material is summarized as follows:
[0060] A. Preparation of nitrogen-doped graphene aerogel;
[0061] B. Preparation of NiCo modified nitrogen-doped graphene aerogel;
[0062] C. Lithium aluminum hydride impregnation of NiCo modified nitrogen-doped graphene aerogel.
[0063] The prepared composite material is named N-rGo@NiCo / LiAlH4, and the mass ratio of each component ranges from N-rGo:NiCo:LiAlH4=15-49.9:0.1-5:50-80. The macroscopic morphology of the composite material is solid nanoparticles.
[0064] The composite material can be widely used in solid-state hydrogen storage materials.
[0065] The present invention will be further described below through several specific embodiments:
[0066] Embodiment 1:
[0067] A method for preparing a N-rGO@NiCo catalyst-loaded LiAlH4 composite material comprises the following steps:
[0068] S1. Preparing nitrogen-doped graphene (N-rGo) aerogel, specifically comprising:
[0069] S101. Configuring a graphene oxide aqueous solution, wherein the concentration of the graphene oxide aqueous solution is 2.5 mg / ml;
[0070] S102. Weigh urea and dissolve it in the graphene oxide aqueous solution, the mass ratio of urea to graphene oxide is 1:3, and then place it in an ultrasonic machine for 2h to obtain solution C;
[0071] S103. Solution C was placed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal treatment at 180° C. for 12 h to obtain a hydrogel;
[0072] S104. Soaking the hydrogel in deionized water for 24 hours, changing the water every 1 hour;
[0073] S105. Obtain the nitrogen-doped graphene aerogel after freeze-drying.
[0074] S2. Preparing NiCo modified nitrogen-doped graphene aerogel, comprising:
[0075] S201. Weigh the obtained nitrogen-doped graphene aerogel and place it in a beaker;
[0076] S202. Weigh the catalyst precursors NiCl2H2O and CoCl26H2O, dissolve them in anhydrous ethanol to form a solution A, pour the solution A into a container containing nitrogen-doped graphene aerogel, and the solution A needs to immerse the nitrogen-doped graphene aerogel;
[0077] S203. The beaker containing solution A was placed on a magnetic stirrer and stirred thoroughly. After ultrasonic treatment for 30 minutes, the anhydrous ethanol in solution A was evaporated and then dried at 80° C. to obtain material B;
[0078] S204. The material B is placed in a corundum crucible and transferred to a tube furnace. Under a nitrogen flow, the temperature is increased from room temperature to 300° C. at a rate of 5° C. per minute and maintained for 6 hours. The material B is then washed with a water-ethanol mixture and filtered three times, and then transferred to an oven at 80° C. for drying to obtain a material C.
[0079] S205. Material C was transferred to the tube furnace again, and the temperature was increased from room temperature to 550° C. at a rate of 2° C. per minute under a nitrogen flow and maintained for 6 h to obtain material D;
[0080] S206. Transfer material D to an argon glove box, remove the adsorbed moisture and other impurity gases in a tube furnace at 150° C. in vacuum to obtain NiCo-modified nitrogen-doped graphene aerogel.
[0081] S3. Lithium aluminum hydride (LiAlH4) impregnation of NiCo modified nitrogen-doped graphene aerogel, specifically comprising:
[0082] S301. Weigh a portion of NiCo modified nitrogen-doped graphene aerogel, weigh the same amount of lithium aluminum hydride and transfer them to a reagent bottle;
[0083] S302. Add the ether dried over calcium hydride and filtered through a 0.45 μm syringe filter into the reagent bottle and stir well to obtain solution B;
[0084] S303. The solution B is drawn into the syringe and impregnated dropwise onto the NiCo-modified nitrogen-doped graphene aerogel to ensure that the NiCo-modified nitrogen-doped graphene aerogel is fully infiltrated;
[0085] S304. The infiltrated NiCo-modified nitrogen-doped graphene aerogel is transferred to a tube furnace and vacuum dried at room temperature for 12 hours, and the vacuum is re-drawn every hour to obtain the final product, which is recorded as N-rGo@NiCo / LiAlH4. The mass ratio of the components of the composite material of this embodiment is N-rGo:NiCo:LiAlH4=49.5:0.5:50, and the macroscopic morphology of the composite material is solid nanoparticles.
[0086] In order to obtain the microscopic morphology of the composite material after loading, the obtained material was characterized by SEM to determine the microscopic morphology of the loaded LiAlH4 and the morphology of graphene. And to determine the effect of large specific surface area materials on the particle size of solution impregnated LiAlH4. The morphology of the NiCo catalyst loaded material was mainly characterized, such as Figure 1 As shown. Graphene and LiAlH4 can be clearly distinguished at low magnifications. Due to the obvious difference in the conductivity of the materials, graphene appears dark in the picture, while LiAlH4 appears grayish white due to its poor conductivity. Graphene shows a loose and porous morphology at low magnifications, and the pore size can be maintained in the micron range. The inside of the graphene is relatively flat, while there are more wrinkles at the edge of the graphene. The morphology of LiAlH4 is highly correlated with graphene, and LiAlH4 is mainly distributed in three forms inside the material. Particles with a size of about 100-200nm are mainly distributed on the flat surface inside the large piece of graphene; some LiAlH4 are evenly distributed on the surface of graphene, showing a morphology attached to the graphene material - a thin film state with a thickness of about 50nm; LiAlH4 material agglomerates at the edge and wrinkle of the graphene, showing micron-sized particles. Among them, nanoparticles will effectively inhibit the separation and diffusion of material elements, which is expected to provide great help to the reversibility of the material. However, the aggregation at the folds will greatly lead to phase separation and diffusion of the material, thereby reducing the effective contact area of the material and causing serious obstacles to the reversibility of the material. But at the same time, it also proves that large-area materials have a significant limiting effect on the particle size of hydrogen storage materials, and it is not necessary to rely on the tiny mesopores of the material itself to achieve the limitation.
[0087] In order to determine the phase structure of the material, XRD characterization was performed on the N-rGo@NiCo composite material before and after loading LiAlH4. The results are as follows Figure 2 As shown. Among them, the corresponding diffraction curve of N-rGo@NiCo shows a diffraction peak of graphene at a bun-shaped position at 25.1°, while the single peaks of Ni and Co do not appear, indicating that Ni and Co may appear in the form of single atoms. The characteristic peak of LiAlH4 is found at 20°, and it corresponds well to the standard card (JCPDS card no. 12-0473), but the structure has changed greatly compared with the original LiAlH4, and the corresponding peak intensity has slightly decreased. It may be that the dissolution and recrystallization during the solution immersion process lead to the difference in the crystal form of the material, but the peak position of the material has not shifted significantly. On different loading matrices, the material produces the XRD peak of Li3AlH6, the hydrogen release product of LiAlH4, and produces a small amount of corresponding diffraction peaks of Al (38.5° and 44°), which indicates that the material may be destabilized and decomposed by the LiAlH4 of the material under the action of the NiCo bimetallic single atom catalyst during the solvent removal process.
[0088] See also Figure 3 The inventors further characterized and analyzed the N-rGo@NiCo sample using a spherical aberration-corrected transmission electron microscope. The image further confirmed the existence form of the catalyst in the material. Figure 3 (a) In the HAADF mode, the morphology of graphene can be clearly seen, with a wrinkled sheet structure. The EDS spectrum analysis of the material shows that Figure 3 It can be seen from (b), 3(c), 3(d), 3(f), 3(g), and 3(h) that within this range, Ni, Co, N, and C are uniformly distributed along with the basic morphology of the material; see Fig.10 At high magnification, after spherical aberration correction, it is obvious that there are some high-brightness points in the material. According to the shooting scale, they can be determined to be single atoms. Under EDS energy spectrum analysis, their composition is determined to be Ni and Co. The high catalytic activity of bimetallic single atoms will greatly improve the dehydrogenation and rehydrogenation performance of the material.
[0089] See also Figure 4 Compared with the initial dehydrogenation temperature of the original LiAlH4 of about 160°C, the dehydrogenation performance of the N-rGo@NiCo / LiAlH4 composite material prepared in Example 1 has been greatly improved, which can significantly reduce the initial dehydrogenation temperature of the material; in order to better reflect the advantages of the NiCo catalyst in this embodiment, the inventors conducted a non-isothermal dehydrogenation performance test on the LiAlH4 composite material with Ni and Co elements loaded separately. The test results are shown in Figure 5 As shown, Figure 5 (a) is the loaded Ni single atom, Figure 5 (b) Loaded Co single atom.
[0090] Table 1 below summarizes the dehydrogenation temperatures of the N-rGo@NiCo / LiAlH4 composite material and the comparative Ni and Co atom-loaded composite materials.
[0091] Table 1
[0092] Composite system Initial dehydrogenation temperature Peak dehydrogenation temperature N-rGo@NiCo 103℃ 123℃ N-rGo@Ni 110℃ 127℃ N-rGo@Co 115℃ 128℃
[0093] It can be seen that compared with single transition metal elements Ni and Co single atoms, the N-rGo@NiCo / LiAlH4 composite material of this embodiment has a lower hydrogen desorption temperature.
[0094] In order to explore the rehydrogenation performance of the composite material, the dehydrogenated N-rGo@NiCo / LiAlH4 composite material was vacuum treated at 300℃ for about 1h to ensure complete dehydrogenation. After treatment, the material was rehydrogenated at 10Mpa and 150℃ for 12h, and then the material was taken out, weighed, and placed back in the reactor for programmed temperature increase to explore the rehydrogenation performance of the material, see Figure 6 For the NiCo catalyst, the rehydrogenation performance of the material is such that the material can release 0.6wt% of the capacity in the range of room temperature to 300°C. Considering that the method adopted is solution impregnation and the material loading is only 50wt%, the reversibility relative to the original LiAlH4 material will reach 1.2wt%.
[0095] To verify the rehydrogenation performance of the composite material, see Figure 7 , characterized by FT-IR of the composite material before and after dehydrogenation, corresponding to 1392cm in FT-IR -1 、890cm -1 and 708cm -1 Certain absorption peaks are also produced at the locations, which proves that a small amount of Li3AlH6 and LiAlH4 are produced during the rehydrogenation process.
[0096] In order to further study the hydrogen desorption rate of the composite material, the isothermal properties of N-rGo@NiCo / LiAlH4 at 80℃, 100℃, 120℃, and 160℃ were measured. Figure 8As shown, the material exhibits excellent isothermal properties. It can slowly release about 1.5wt% hydrogen at a low temperature of 80°C. At 120°C, the original material can only release about 0.5wt% hydrogen, and the material can reach a capacity of about 2wt% when the loading rate is 50wt%, which is about 8 times the amount of hydrogen released at this temperature as the original LiAlH4. And the amount of hydrogen released by the material reaches the maximum value within 90min. It can be seen that N-rGo@NiCo / LiAlH4 can significantly promote the dehydrogenation kinetics of the material.
[0097] In order to more quantitatively study the kinetic properties of the material, it is planned to use the heat signal at different heating rates to test the dehydrogenation performance of the material at different heating rates, and to fit the apparent activation energy according to the Kissinger equation. Fig. 9 . However, due to the large size of the material caused by the graphene surface loaded, the data analysis in differential scanning calorimetry (DSC) is not clear. Therefore, the programmed temperature coupled mass spectrometry test technology is adopted to obtain the curve of hydrogen release of the material under multiple heating rate conditions, and match it with the programmed temperature data to obtain the peak temperature of material dehydrogenation. Fitting these data can obtain the activation energy of hydrogen release of the material and reflect its kinetic properties from an intuitive level. By testing NiCo at different heating rates of 3K / min, 5K / min, and 10K / min, and comparing it with the programmed temperature data, as shown in the figure. Fig. 9 As shown in the figure, NiCo has two dehydrogenation peaks in the range of 120℃-210℃, which matches the dehydrogenation temperature of the original material. Compared with the dehydrogenation temperature of pure LiAlH4 of 170℃-250℃ in the literature, it is significantly lower. Recording the corresponding peak data and fitting the calculation through the Kissinger equation, it can be concluded that the apparent activation energy of the two-step dehydrogenation of the N-rGo@NiCo / LiAlH4 sample is 78.95 kJ·mol -1 and 110.65 kJ·mol -1 , compared with the apparent activation energy of LiAlH4 reported in the relevant literature, it is reduced by 42.2 kJ·mol -1 and 51.53 kJ·mol -1 .
[0098] Embodiment 2:
[0099] A method for preparing a N-rGO@NiCo catalyst-loaded LiAlH4 composite material comprises the following steps:
[0100] S1. Preparing nitrogen-doped graphene (N-rGo) aerogel, specifically comprising:
[0101] S101. Configuring a graphene oxide aqueous solution, wherein the concentration of the graphene oxide aqueous solution is 1 mg / ml;
[0102] S102. Weigh urea and dissolve it in the graphene oxide aqueous solution, the mass ratio of urea to graphene oxide is 10:1, and then place it in an ultrasonic machine for 0.5h to obtain solution C;
[0103] S103. Solution C was placed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal treatment at 120° C. for 48 h to obtain a hydrogel;
[0104] S104. Soaking the hydrogel in deionized water for 6 h, changing the water every 0.5 h;
[0105] S105. Obtain the nitrogen-doped graphene aerogel after freeze-drying.
[0106] S2. Preparing NiCo modified nitrogen-doped graphene aerogel, comprising:
[0107] S201. Weigh the obtained nitrogen-doped graphene aerogel and place it in a beaker;
[0108] S202. Weigh the catalyst precursors Ni(NO3)2 and Co(NO3)2, dissolve them in anhydrous ethanol to form a solution A, and pour the solution A into a container containing nitrogen-doped graphene aerogel, wherein the solution A needs to immerse the nitrogen-doped graphene aerogel;
[0109] S203. The beaker containing solution A was placed on a magnetic stirrer and stirred thoroughly. After ultrasonic treatment for 30 minutes, the anhydrous ethanol in solution A was evaporated and then dried at 45° C. to obtain material B;
[0110] S204. The material B is placed in a corundum crucible and transferred to a tube furnace. Under an argon gas flow, the temperature is increased from room temperature to 150° C. at a rate of 5° C. per minute and maintained for 10 hours. The material B is then washed with a water-ethanol mixture and filtered three times, and then transferred to an oven at 80° C. for drying to obtain a material C.
[0111] S205. Material C was transferred to the tube furnace again, and the temperature was increased from room temperature to 400° C. at a rate of 5° C. per minute under an argon gas flow and maintained for 10 h to obtain material D;
[0112] S206. Transfer material D to an argon glove box, remove the adsorbed moisture and other impurity gases in a tube furnace at 60°C in vacuum to obtain NiCo-modified nitrogen-doped graphene aerogel.
[0113] S3. Lithium aluminum hydride (LiAlH4) impregnation of NiCo modified nitrogen-doped graphene aerogel, specifically comprising:
[0114] S301. Weigh a portion of NiCo modified nitrogen-doped graphene aerogel, weigh the same amount of lithium aluminum hydride and transfer them to a reagent bottle;
[0115] S302. Add the ether dried over calcium hydride and filtered through a 0.45 μm syringe filter into the reagent bottle and stir well to obtain solution B;
[0116] S303. The solution B is drawn into the syringe and impregnated dropwise onto the NiCo-modified nitrogen-doped graphene aerogel to ensure that the NiCo-modified nitrogen-doped graphene aerogel is fully infiltrated;
[0117] S304. The infiltrated NiCo-modified nitrogen-doped graphene aerogel is transferred to a tube furnace and vacuum dried at room temperature for 12 hours, and the vacuum is re-drawn every hour to obtain the final product, which is recorded as N-rGo@NiCo / LiAlH4. The mass ratio of the components of the composite material of this embodiment is N-rGo:NiCo:LiAlH4=27:3:70, and the macroscopic morphology of the composite material is solid nanoparticles.
[0118] Embodiment 3:
[0119] A method for preparing a N-rGO@NiCo catalyst-loaded LiAlH4 composite material comprises the following steps:
[0120] S1. Preparing nitrogen-doped graphene (N-rGo) aerogel, specifically comprising:
[0121] S101. Configuring a graphene oxide aqueous solution, wherein the concentration of the graphene oxide aqueous solution is 10 mg / ml;
[0122] S102. Weigh urea and dissolve it in the graphene oxide aqueous solution, the mass ratio of urea to graphene oxide is 1:10, and then place it in an ultrasonic machine for 5 hours to obtain a solution C;
[0123] S103. Solution C was placed in a polytetrafluoroethylene hydrothermal reactor and subjected to hydrothermal treatment at 200° C. for 12 h to obtain a hydrogel;
[0124] S104. Soaking the hydrogel in deionized water for 72 h, changing the water every 10 h;
[0125] S105. Obtain the nitrogen-doped graphene aerogel after freeze-drying.
[0126] S2. Preparing NiCo modified nitrogen-doped graphene aerogel, comprising:
[0127] S201. Weigh the obtained nitrogen-doped graphene aerogel and place it in a beaker;
[0128] S202. Weigh the catalyst precursors Co(CH3COO)2 and Ni(CH3COO)2, dissolve them in anhydrous ethanol to form a solution A, pour the solution A into a container containing nitrogen-doped graphene aerogel, and the solution A needs to immerse the nitrogen-doped graphene aerogel;
[0129] S203. The beaker containing solution A was placed on a magnetic stirrer and stirred thoroughly. After ultrasonic treatment for 30 minutes, the anhydrous ethanol in solution A was evaporated and then dried at 150° C. to obtain material B;
[0130] S204. The material B is placed in a corundum crucible and transferred to a tube furnace. Under a nitrogen flow, the temperature is increased from room temperature to 500° C. at a rate of 5° C. per minute and maintained for 3 hours. The material B is then washed with a water-ethanol mixture and filtered three times, and then transferred to an oven at 80° C. for drying to obtain a material C.
[0131] S205. Material C was transferred to the tube furnace again, and the temperature was increased from room temperature to 750° C. at a rate of 10° C. per minute under nitrogen flow and maintained for 3 h to obtain material D;
[0132] S206. Transfer material D to an argon glove box, remove the adsorbed moisture and other impurity gases in a tube furnace at 200° C. in vacuum to obtain NiCo-modified nitrogen-doped graphene aerogel.
[0133] S3. Lithium aluminum hydride (LiAlH4) impregnation of NiCo modified nitrogen-doped graphene aerogel, specifically comprising:
[0134] S301. Weigh a portion of NiCo modified nitrogen-doped graphene aerogel, weigh the same amount of lithium aluminum hydride and transfer them to a reagent bottle;
[0135] S302. Add the ether dried over calcium hydride and filtered through a 0.45 μm syringe filter into the reagent bottle and stir well to obtain solution B;
[0136] S303. The solution B is drawn into the syringe and impregnated dropwise onto the NiCo-modified nitrogen-doped graphene aerogel to ensure that the NiCo-modified nitrogen-doped graphene aerogel is fully infiltrated;
[0137] S304. The infiltrated NiCo-modified nitrogen-doped graphene aerogel is transferred to a tube furnace and vacuum dried at room temperature for 12 hours, and the vacuum is re-drawn every hour to obtain the final product, which is recorded as N-rGo@NiCo / LiAlH4. The mass ratio of the components of the composite material of this embodiment is N-rGo:NiCo:LiAlH4=15:5:80, and the macroscopic morphology of the composite material is solid nanoparticles.
[0138] The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not intended to limit the present invention. For those skilled in the art, according to the concept of the present invention, some simple deductions, modifications or substitutions can be made.
Claims
1. N-rGO@NiCo catalyst loaded LiAlH4 composite material, characterized in that: The composite material is named N-rGO@NiCo / LiAlH4, the mass ratio of each component ranges from N-rGO:NiCo:LiAlH4=15-49.9:0.1-5:50-80, and the macroscopic morphology of the composite material is solid nanoparticles; The preparation method of the N-rGO@NiCo catalyst-loaded LiAlH4 composite material comprises: S1. Preparation of nitrogen-doped graphene aerogel; S2. Preparing NiCo modified nitrogen-doped graphene aerogel, comprising: S201. Weigh the nitrogen-doped graphene aerogel and place it in a container; S202. Weigh the nickel source and cobalt source precursors of the catalyst, dissolve them in anhydrous ethanol to form a solution A, and pour the solution A into the container containing the nitrogen-doped graphene aerogel, so that the solution A submerges the nitrogen-doped graphene aerogel; S203. Place the container containing solution A on a magnetic stirrer and stir thoroughly. After ultrasonic treatment for 30 minutes, evaporate the anhydrous ethanol in solution A, and then dry at 45-150°C to obtain material B. S204. Place the material B in a porcelain boat and transfer it to a tube furnace. In an argon or nitrogen atmosphere, heat the material from room temperature to 150-500°C at a rate of 2-10°C per minute and maintain the temperature for 3-10 hours. Wash the material with a water-ethanol mixture and filter it three times. Transfer the material to an oven at 80°C and dry it to obtain material C. S205. Transfer the material C to a tube furnace again, and heat the temperature from room temperature to 400-750°C at a rate of 2-10°C per minute under an argon or nitrogen flow and maintain the temperature for 3-10 hours to obtain material D; S206. Transfer material D to an argon glove box, remove the adsorbed moisture in a tube furnace at 60-200° C. in vacuum to obtain NiCo-modified nitrogen-doped graphene aerogel; S3. Perform lithium aluminum hydride impregnation of the NiCo modified nitrogen-doped graphene aerogel.
2. According to claim 1, the N-rGO@NiCo catalyst-loaded LiAlH4 composite material is characterized in that: The mass ratio of each component is: N-rGo:NiCo:LiAlH4=49.5:0.5:
50.
3. The N-rGO@NiCo catalyst-loaded LiAlH4 composite material according to claim 1, characterized in that: The NiCo is in the form of bimetallic single atoms.
4. The method for preparing the N-rGO@NiCo catalyst-loaded LiAlH4 composite material according to any one of claims 1 to 3, characterized in that: include: S1. Preparation of nitrogen-doped graphene aerogel; S2. Preparing NiCo modified nitrogen-doped graphene aerogel, comprising: S201. Weigh the nitrogen-doped graphene aerogel and place it in a container; S202. Weigh the nickel source and cobalt source precursors of the catalyst, dissolve them in anhydrous ethanol to form a solution A, and pour the solution A into the container containing the nitrogen-doped graphene aerogel, so that the solution A submerges the nitrogen-doped graphene aerogel; S203. Place the container containing solution A on a magnetic stirrer and stir thoroughly. After ultrasonic treatment for 30 minutes, evaporate the anhydrous ethanol in solution A, and then dry at 45-150°C to obtain material B. S204. Place the material B in a porcelain boat and transfer it to a tube furnace. In an argon or nitrogen atmosphere, heat the material from room temperature to 150-500°C at a rate of 2-10°C per minute and maintain the temperature for 3-10 hours. Wash the material with a water-ethanol mixture and filter it three times. Transfer the material to an oven at 80°C and dry it to obtain material C. S205. Transfer the material C to a tube furnace again, and heat the temperature from room temperature to 400-750°C at a rate of 2-10°C per minute under an argon or nitrogen flow and maintain the temperature for 3-10 hours to obtain material D; S206. Transfer material D to an argon glove box, remove the adsorbed moisture in a tube furnace at 60-200° C. in vacuum to obtain NiCo-modified nitrogen-doped graphene aerogel; S3. performing lithium aluminum hydride impregnation of the NiCo modified nitrogen-doped graphene aerogel.
5. The preparation method according to claim 4, characterized in that: S1. Preparing nitrogen-doped graphene aerogel, comprising: S101. preparing a graphene oxide aqueous solution, wherein the concentration of the graphene oxide aqueous solution is 1-10 mg / ml; S102. Weigh urea or melamine and dissolve it in the graphene oxide aqueous solution, wherein the mass ratio of urea to graphene oxide is 10-0.1:1, and then place it in an ultrasonic machine for 0.5-5 hours to obtain solution C; S103. Place solution C in a hydrothermal reactor and perform hydrothermal treatment at 120-200° C. for 12-48 h to obtain a hydrogel; S104. Soaking the hydrogel in deionized water for 6-72 hours, changing the water every 0.5-5 hours; S105. After freeze drying, the nitrogen-doped graphene aerogel is obtained.
6. The preparation method according to claim 4, characterized in that: S3. Carrying out lithium aluminum hydride impregnation of the NiCo modified nitrogen-doped graphene aerogel, comprising: S301. Weigh lithium aluminum hydride and transfer it to a reagent bottle; S302. Add the dried and filtered calcium hydride into the reagent bottle with diethyl ether and stir thoroughly to obtain solution B; S303. The solution B is drawn into the syringe and impregnated dropwise onto the NiCo modified nitrogen-doped graphene aerogel to ensure that the NiCo modified nitrogen-doped graphene aerogel is fully infiltrated; S304. The infiltrated NiCo-modified nitrogen-doped graphene aerogel was transferred to a tube furnace and vacuum dried at room temperature for 12 h to obtain the final product.
7. The N-rGO@NiCo catalyst-loaded LiAlH4 composite material according to claim 6, characterized in that: Before taking out the final product, the attached ether was removed by heating the tube furnace at 40-90°C.
8. Use of the composite material according to any one of claims 1 to 3 or the composite material prepared by the preparation method according to any one of claims 4 to 7 in solid hydrogen storage materials.
Citation Information
Patent Citations
Hydrogen storage material based on LiAlH4 and preparation method thereof
CN108658038A
LITHIATION INDUCED POROUS Pd NANOPARTICLE / 3D GRAPHENE AEROGEL COMPOSITE FOR HIGHLY REVERSIBLE HYDROGEN STORAGE BASED ON SPILLOVER PROCESS
US20230150813A1